2018
DOI: 10.3389/fmicb.2018.00780
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Custom MALDI-TOF MS Database for Species-Level Identification of Bacterial Isolates Collected From Spacecraft and Associated Surfaces

Abstract: Since the 1970s, the Planetary Protection Group at the Jet Propulsion Laboratory (JPL) has maintained an archive of spacecraft-associated bacterial isolates. Identification of these isolates was routinely performed by sequencing the 16S rRNA gene. Although this technique is an industry standard, it is time consuming and has poor resolving power for some closely related taxa. Matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) mass spectrometry is widely used in clinical diagnostics and is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 33 publications
2
39
0
Order By: Relevance
“…The bacteria E. faecium was isolated from healthy A. gigas , selected by in vitro assays by our research group according to Mouriño et al (), identified by MALDI‐TOF mass spectrometry (Microflex) (Seuylemezian et al, ), with identification confirmed using a molecular approach by Neoprospecta microbiome technologies (Santa Catarina State, Brazil). This study was approved by an Ethics Committee for Animal Experimentation (CEUA/172008FAPESPA01).…”
Section: Methodsmentioning
confidence: 99%
“…The bacteria E. faecium was isolated from healthy A. gigas , selected by in vitro assays by our research group according to Mouriño et al (), identified by MALDI‐TOF mass spectrometry (Microflex) (Seuylemezian et al, ), with identification confirmed using a molecular approach by Neoprospecta microbiome technologies (Santa Catarina State, Brazil). This study was approved by an Ethics Committee for Animal Experimentation (CEUA/172008FAPESPA01).…”
Section: Methodsmentioning
confidence: 99%
“…Although molecular methods have failed up to separate P. freudenreichii subspecies, MALDI-TOF analysis has been successful method for characterization of intraspecific differences (subspecies, strains) (Vorob'eva et al, 2011). Because MALDI-TOF MS provides more detailed protein profile than what is signified by the 16S rRNA gene, it can detect strain-level differences among isolate samples (Seuylemezian et al, 2018). The MALDI spectra of the samples revealed that there were characteristic protein groups belong to Propionibacterium as marker biomolecules (Vorob'eva et al, 2011); therefore, they can be differentiated easily.…”
Section: Resultsmentioning
confidence: 99%
“…The standard contained a carefully manufactured extract of this microorganism that shows a characteristic peptide and protein profile in MALDI-TOF MS spectra. The detected spectrum peaks correspond to the mass of the most abundant proteins in a sample which turns out to be specific for the analysed microbial species (Singhal et al ., 2015; Seuylemezian et al ., 2018). Thus, identification occurs automatically using software Bruker Biotyper MS version 3 which is responsible to compare the spectral profile of tested microorganism with a reference database DB 7311.…”
Section: Methodsmentioning
confidence: 99%